An effective estimation strategy for significant wave height via independent component analysis. (15th April 2022) - Wu, Fan; Wang, Wei; Hu, Ziying; Wang, Xianpeng
Abstract: In this paper, an effective significant wave height (SWH) estimation method of X-band radar image sequences based on independent component analysis (ICA) is proposed. Radial direction data is first selected from the radar image, and then the original components of ocean waves are obtained via the ICA theory. Considering the formation mechanism of ocean waves, the relationship between SWH and energy of ocean waves is explored, which is propitious for a more effective estimation of wave height. Finally, by adopting the fitted relationship, SWH is estimated by calculating the energy of waves. The proposed method is tested by the simulated data and the real data. The results show that the proposed method achieves better correlation coefficient between the real value and the estimation value, which is more than 92%. The root mean squared error (RMSE) is lower than the EOF-based method and the EEMD-based method. The results indicate that the performance of the proposed method has been improved in terms of significant wave height estimation. Highlights: The original components of ocean wave can be acquired from radar image sequences based on wave composition and ICA techniques. The relationship between the significant wave height and the energy of original component is derived, and the coefficients are fitted with the data. Relevant simulation and experiments are employed to verify the accurate performance for wave height estimation via the method.